PENGARUH INTENSITAS KOMUNIKASI ANTAR PETERNAK TERHADAP PRODUKTIVITAS AYAM RAS PETELUR DI KECAMATAN PENEBEL KABUPATEN TABANAN - Syamsudin, H. A.,; I G. Suarta,; N. W. T. Inggriati,; I N. Suparta (Jurnal Peternakan Tropika, 2025)
Indonesia, as an agricultural country, has an important livestock sector, especially infulfilling animal protein. Laying hens are one of the main commodities, with productioncontinuing to increase. Bali Province, especially Tabanan Regency and Penebel District, hasgreat potential in developing laying hen farms, but its productivity is still hampered by limitedaccess to information, low participation in farmer groups, and communication constraintsbetween farmers. This study used a sample of 36 farmers selected using stratified randomsampling based on business scale (small, medium, large) to examine the effect of communicationintensity on laying hen productivity in Penebel District. Data analysis used the Spearman rankcorrelation test with qualitative and quantitative descriptive techniques. The results showed thatthe level of communication intensity including frequency (60.22%), time (64%), and attention(76%) was quite good. However, the correlation analysis showed a weak negative relationshipbetween communication variables (frequency, time, attention, tolerance, supportive attitude,open attitude, equality, response) and egg productivity (r= -0.133 to -0.014; *p* > 0.05). Onlytolerance has a significant effect on communication intensity. This finding indicates thatproductivity is more influenced by other factors such as feed quality, cage management, andchicken health, compared to communication intensity. Further research is needed to identifyfactors supporting productivity and formulate effective communication strategies for farmers. ABSTRAK Indonesia, sebagai negara agraris, memiliki sektor peternakan yang penting, terutamadalam pemenuhan protein hewani. Ayam ras petelur menjadi salah satu komoditas utama, denganproduksi yang terus meningkat. Provinsi Bali, khususnya Kabupaten Tabanan dan KecamatanPenebel, memiliki potensi besar dalam pengembangan peternakan ayam ras petelur, namunproduktivitasnya masih terhambat oleh keterbatasan akses informasi, rendahnya partisipasidalam kelompok tani, dan kendala komunikasi antar peternak. Penelitian ini menggunakansampel sebanyak 36 peternak yang dipilih secara stratified random sampling berdasarkan skalausaha (kecil, sedang, besar) untuk mengkaji pengaruh intensitas komunikasi terhadapproduktivitas ayam petelur di Kecamatan Penebel. Analisis data menggunakan uji korelasi rankSpearman dengan teknik deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkanbahwa tingkat intensitas komunikasi yang meliputi frekuensi (60,22%), waktu (64%), danperhatian (76%) tergolong cukup baik. Namun, analisis korelasi menunjukkan hubungan negatiflemah antara variabel komunikasi (frekuensi, waktu, perhatian, toleransi, sikap suportif, sikapterbuka, kesetaraan, respons) dengan produktivitas telur (r = -0,133 hingga -0,014; *p* > 0,05).Hanya toleransi yang berpengaruh signifikan terhadap intensitas komunikasi. Temuan inimengindikasikan bahwa produktivitas lebih dipengaruhi faktor lain seperti kualitas pakan,manajemen kandang, dan kesehatan ayam, dibandingkan intensitas komunikasi. Penelitian lebihlanjut diperlukan untuk mengidentifikasi faktor pendukung produktivitas serta merumuskanstrategi komunikasi yang efektif bagi peternak.